Measurements of body fat distribution: assessment of collinearity with body mass, adiposity and height in female adolescents - Pereira, Patrícia Feliciano (2015)
To verify the correlation between body fat location measurements with the body mass index (BMI), body fat percentage (BF%) and height, according to the nutritional status in female adolescents. A controlled cross-sectional study was carried out with 113 adolescents (G1: 38 with normal weight, but with high body fat level, G2: 40 with normal weight and G3: 35 overweight) from public schools in Viçosa-MG, Brazil. The following measures were assessed: weight, height, waist circumference (WC), umbilical circumference (UC), hip circumference (HC), thigh circumference, waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), waist-to-thigh ratio (WTR), conicity index (CI), sagittal abdominal diameter (SAD), coronal diameter (CD), central (CS) and peripheral skinfolds (PS). The BF% was assessed by tetrapolar electric bioimpedance. The increase in central fat, represented by WC, UC, WHtR, SAD, CD and CS, and the increase in peripheral fat indicated by HC and thigh circumference were proportional to the increase in BMI and BF%. WC and especially the UC showed the strongest correlations with adiposity. Weak correlation between WHR, WTR, CI and CS/PS with adiposity were observed. The height showed correlation with almost all the fat location measures, being fair or weak with waist measurements. The results indicate colinearity between body mass and total adiposity with central and peripheral adipose tissue. We recommend the use of UC for assessing nutritional status of adolescents, as it showed the highest capacity to predict adiposity in each group, and also showed fair or weak correlation with height.